Standardisation et différenciation des emplois des emoji sur Facebook : observations à partir d’un exercice pédagogique en DUT - Justine Le Floc’h (Communiquer)
Examining emojis in their enunciation context in a corpus of French-speaking Facebook pages in October 2018, this article shows how a grammar of emojis can emerges from the use community managers make of them. Emojis show a rhetorical and marketing potential to hold readers’ attention and to increase its engagement both central to maintain reader’s loyalty to the brands. This digital affective labour, as Camille Alloing and Julien Pierre identified it, is related to a general process of normalization: implicit norms of emojis’ use are built up. Nevertheless, those rules do not wipe out the possibility for the brands to keep a free hand on its use of this tool and to create a singular lexicon, depending on its strategy of e-reputation and differentiation.